miR-7 Regulates GLP-1-Mediated Insulin Release by Targeting β-Arrestin 1 - Matarese, Alessandro (Cells, 2020)
Glucagon-like peptide-1 (GLP-1) has been shown to potentiate glucose-stimulated insulin secretion binding GLP-1 receptor on pancreatic β cells. β-arrestin 1 (βARR1) is known to regulate the desensitization of GLP-1 receptor. Mounting evidence indicates that microRNAs (miRNAs, miRs) are fundamental in the regulation of β cell function and insulin release. However, the regulation of GLP-1/βARR1 pathways by miRs has never been explored. Our hypothesis is that specific miRs can modulate the GLP-1/βARR1 axis in β cells. To test this hypothesis, we applied a bioinformatic approach to detect miRs that could target βARR1; we identified hsa-miR-7-5p (miR-7) and we validated the specific interaction of this miR with βARR1. Then, we verified that GLP-1 was indeed able to regulate the transcription of miR-7 and βARR1, and that miR-7 significantly regulated GLP-1-induced insulin release and cyclic AMP (cAMP) production in β cells. Taken together, our findings indicate, for the first time, that miR-7 plays a functional role in the regulation of GLP-1-mediated insulin release by targeting βARR1. These results have a decisive clinical impact given the importance of drugs modulating GLP-1 signaling in the treatment of patients with type 2 diabetes mellitus.